Preparation and application of hydrodechlorination catalyst
By using granular activated carbon as a support in the Cu-Pd catalyst and carrying out specific treatment steps, a hydrodechlorination catalyst with low metal load, low reaction temperature and controllable selectivity for the product was prepared, which solved the problems of fast deactivation, poor stability and high usage cost of the existing catalysts, and achieved efficient catalytic effect and low cost preparation.
Patent Information
- Application Number
- CN202411597823.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-11
- Publication Date
- 2025-03-28
AI Technical Summary
The existing Cu-Pd catalysts used for hydrodechlorination of CFC-113 have problems such as fast catalyst deactivation, poor stability and high usage costs, and it is difficult to take into account both the simple preparation and the low overall cost.
Using granular activated carbon as a support, a hydrodechlorination catalyst with low metal load, low reaction temperature and controllable selectivity of the product was prepared by impregnating the palladium source and copper source on the activated carbon support, and pretreatment, reduction and passivation treatment.
The high selectivity and long life of the catalyst are achieved, the total selectivity of the hydrogenation products chloroethylene and trifluoroethylene exceeds 98%, and the product selectivity is controlled by adjusting the reduction temperature and support carbon source type, reducing the production cost of the catalyst.
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of fluorine chemical industry and relates to the preparation and application of a hydrodechlorination catalyst. Background Art
[0002] In the field of fluorine chemical industry, chlorofluoroalkanes are precious resources. In the context of environmental and atmospheric protection, the use of hydrodechlorination to prepare fluorinated olefins is an effective way to transform chlorofluoroalkanes into high value-added downstream products. It is in line with the development direction of green and environmentally friendly chemical industry. The hydrogenation process route is simple and easy to achieve large-scale industrialization.
[0003] Chlorotrifluoroethylene (CTFE) and trifluoroethylene (TrFE) are key monomers for the synthesis of fluorine-containing materials such as fluororubber, fluororesin and fluorocoatings, and are also one of the important raw materials for fluorine-containing fine chemicals. Currently, the industry mainly uses zinc powder reduction or hydrogenation reduction of 1,1,2-trifluorotrichloroethane (CFC-113) to produce CTFE, and CTFE can be further hydrogenated to produce TrFE.
[0004] For the hydrodechlorination reaction of CFC-113, Chinese patent CN1065261A discloses a type of activated carbon-supported Cu and Pd catalyst and preparation method, which can significantly improve the conversion rate of CFC-13 and the selectivity of hydrogenation to CTFE and TrFE, and by increasing the proportion of copper, the selectivity of CTFE can be improved, thereby achieving the purpose of controlling the selectivity distribution of CTFE and TrFE, but the overall reaction performance of the catalyst, especially the stability, still needs to be improved.
[0005] Chinese patent CN1460549A publicly reports a type of activated carbon-supported Cu-Pd-based catalyst, which can further improve the selectivity of CFC-113 hydrogenation to CTFE and the stability of the catalyst by adding alkali metals and rare earth metals. However, the low-temperature activity of the catalyst and the selectivity distribution of fluorinated olefins CTFE and TrFE still need to be improved.
[0006] Chinese patent CN 112657527 discloses a Cu-Pd non-alloy catalyst supported by nitrogen-doped activated carbon and carbon nitride, which has high selectivity for chlorotrifluoroethylene and low selectivity for trifluoroethylene, and the catalyst life can reach more than 1000 hours. The palladium content of the catalyst is 0.5-10%, and the copper content is 2-10%. After passivation and programmed temperature ammoniation treatment, palladium and copper are dispersed on the carrier surface in a non-alloy phase.
[0007] Chinese patent CN112007657 discloses a Cu-Pd alloy catalyst for dechlorination reaction, and its selectivity for producing trifluorochloroethylene by hydrogenation dechlorination of CFC-113 can reach 90%. The catalyst is prepared by distributed impregnation, and ammonia activation is the key to obtain the alloy Cu-Pd. The carrier activated carbon is treated with nitrogen atmosphere above 400°C, which is beneficial to the improvement of the surface properties of the activated carbon and the dispersed loading of the alloy.
[0008] Therefore, from the perspective of the existing Cu-Pd system catalysts used for CFC-113 hydrodechlorination, the activity, precious metal loading and life of the catalyst have been improved to a certain extent. However, there are still certain limitations and difficulties in achieving a catalyst with simple preparation and low overall cost, and in achieving an adjustable selectivity ratio of CFC-113 hydrogenation to prepare chlorotrifluoroethylene and trifluoroethylene through the carrier and preparation conditions. Summary of the invention
[0009] The purpose of the present invention is to provide a preparation and application of a hydrodechlorination catalyst, which has the advantages of low metal loading, low reaction temperature and controllable product selectivity. The use of granular activated carbon can avoid the influence of activated carbon extrusion molding and molding aids on catalyst preparation and performance. At the same time, the catalyst can be used for the hydrodechlorination reaction of CFC-113, which can solve the problems of rapid deactivation, poor stability and high use cost of the previous catalyst, and provide an effective way to convert chlorofluoroalkanes into fluorinated olefins.
[0010] The purpose of the present invention can be achieved by the following technical solutions:
[0011] The first aspect of the present invention provides a method for preparing a hydrodechlorination catalyst, comprising: impregnating a palladium source and a copper source on an activated carbon carrier, drying, and sequentially performing a heating pretreatment in an inert atmosphere, a reduction treatment in a hydrogen atmosphere, and a passivation treatment in an air atmosphere;
[0012] The loading amount of palladium on the activated carbon carrier is 0.5-0.1 wt %, and the loading amount of copper on the activated carbon carrier is 5-0.1 wt %.
[0013] Furthermore, the specific surface area of the activated carbon carrier is 500 to 1200 cm 2 / g, pore volume 0.5~2m 3 / g, average pore size 1-8nm, ash content less than 0.5-15wt%;
[0014] As a preferred technical solution, the specific surface area of the activated carbon carrier is 600 to 1000 cm 2 / g, pore volume 0.6~1.2m 3 / g, average pore size 2-5nm, ash content less than 0.5-10wt%;
[0015] The carbon source of the activated carbon carrier is selected from at least one of coal, coconut shell, fruit shell, asphalt or phenolic resin.
[0016] As a preferred technical solution, the carbon source of the activated carbon carrier is selected from coal, coconut shell or phenolic resin, and coconut shell is more preferred.
[0017] Furthermore, the palladium source and the copper source are loaded on the activated carbon carrier by co-impregnation or step-by-step impregnation; when step-by-step impregnation is adopted, the copper source is loaded first, and then the palladium source is loaded after drying.
[0018] Furthermore, the impregnation may be performed by equal volume impregnation or solution spray impregnation.
[0019] Furthermore, the pH of the impregnating solution or salt solution used is less than 1, and the pH is preferably adjusted using nitric acid or hydrochloric acid.
[0020] Furthermore, the palladium source is selected from at least one of palladium chloride, palladium nitrate or palladium acetate; the copper source is selected from at least one of copper nitrate, cupric chloride, cuprous chloride, cupric acetate or copper sulfate.
[0021] Furthermore, the loading amount of palladium on the activated carbon carrier is 0.5-0.2wt%, and more preferably 0.5-0.3wt%; the loading amount of copper on the activated carbon carrier is 5-0.5wt%, and more preferably 5-1.5wt%.
[0022] Furthermore, the drying adopts at least one of normal pressure drying, negative pressure vacuum drying and microwave drying, and the drying temperature is 40-100°C, and the preferred drying temperature is 60-80°C.
[0023] Furthermore, in the heating pretreatment, the pretreatment temperature is 100-600° C., preferably 200-500° C., and more preferably 300-400° C.; the inert atmosphere is nitrogen or argon, preferably nitrogen.
[0024] Furthermore, in the reduction treatment, the reduction temperature is 250-600°C, preferably 300-550°C, and more preferably 350-500°C.
[0025] Furthermore, in the passivation treatment, the treatment temperature is room temperature to 150°C.
[0026] A second aspect of the present invention provides an application of a hydrodechlorination catalyst, comprising using the hydrodechlorination catalyst for the hydrogenation reduction reaction of 1,1,2-trifluorotrichloroethane.
[0027] Furthermore, in the hydrogenation reduction reaction of 1,1,2-trifluorotrichloroethane, the reaction temperature is 100-300°C and the mass space velocity is 0.1-2h-1 , the molar ratio of hydrogen to 1,1,2-trifluorotrichloroethane is 1 to 20:1.
[0028] As a preferred technical solution, in the hydrogenation reduction reaction of 1,1,2-trifluorotrichloroethane, the reaction temperature is 130-250°C, and the mass space velocity is 0.2-1.2h -1 , the molar ratio of hydrogen to 1,1,2-trifluorotrichloroethane is 1 to 10:1.
[0029] More preferably, the reaction temperature is 150-200°C, and the mass space velocity is 0.3-0.6h -1 , the molar ratio of hydrogen to 1,1,2-trifluorotrichloroethane is 1.5 to 5:1.
[0030] Compared with the prior art, the present invention has the following characteristics:
[0031] 1) Compared with the Cu-Pd catalytic system in the prior art, the catalyst of the present invention does not require the introduction of additional alkali / alkaline earth metals and rare earth metal additives, has the advantages of low metal loading and high low-temperature reaction activity, and simplifies the catalyst preparation process;
[0032] 2) The catalyst of the present invention has high catalytic selectivity, and the total selectivity of the hydrogenation products chlorotrifluoroethylene and trifluoroethylene is greater than 98%. The product selectivity can be adjusted and controlled by reducing temperature, carrier carbon source type, etc., rather than by conventional Cu-Pd ratio and additive addition. This helps the adsorption and desorption of fluorine and chlorine materials on the catalyst surface, improves the hydrogen dissociation efficiency, and can effectively reduce the occurrence of defluorination side reactions when used in CFC-113 hydrogenation reaction;
[0033] 3) The catalyst of the present invention directly uses granular activated carbon as a carrier, which can avoid the influence of activated carbon extrusion molding and molding aids on catalyst preparation and performance. The carrier has no post-modification and post-doping, which is conducive to reducing the preparation cost of the catalyst. DETAILED DESCRIPTION
[0034] The present invention is described in detail below in conjunction with specific embodiments. This embodiment is implemented based on the technical solution of the present invention, and provides a detailed implementation method and a specific operation process, but the protection scope of the present invention is not limited to the following embodiments.
[0035] In the following examples, unless otherwise specified, raw materials, reagents or processing techniques are all conventional commercial products or conventional processing techniques in the art.
[0036] Catalyst evaluation performance evaluation uses a fixed bed continuous reactor, weighing 100 mL of catalyst in the reactor, heating to 80°C to dry the catalyst for 4 hours, then cooling to below 60°C; then introducing hydrogen for reduction, the reduction process uses a program temperature increase, maintaining at 300°C for 4 hours and then dropping to the reaction temperature. Then, at the reaction temperature, introduce trifluorotrichloroethane and hydrogen, the molar ratio of hydrogen to trifluorotrichloroethane is 3:1, and the mass space velocity of the alkane is 0.6h -1 The reaction product was washed with water and dried. The product was analyzed by gas chromatography, and the conversion rate of trifluorotrichloroethane and the selectivity of trifluorochloroethylene and trifluoroethylene were calculated by the chromatographic peak area normalization method.
[0037] Embodiment 1:
[0038] A hydrodechlorination catalyst, the preparation method of which comprises:
[0039] S1: Coconut shell activated carbon particles (irregular particles with a particle size of 2 to 3 mm, Shanghai Sinopharm Reagent Co., Ltd.) were washed and dried three times with 8%wt nitric acid. The specific surface area of the activated carbon after acid washing was 1200m 2 / g, pore volume 0.8cm 3 / g, pore size 2-4nm, ash content 6wt% (mainly containing oxides of elements such as silicon, iron and aluminum);
[0040] S2: Weigh 5.7 g of copper nitrate trihydrate and 0.25 g of palladium chloride respectively, dissolve in 52 ml of water, and add 1 ml of hydrochloric acid to adjust the pH to 0.9; impregnate 50 g of granular activated carbon with the above solution. After immersion at room temperature for 3 hours, place in a vacuum drying oven at 70°C and dry for 30 minutes;
[0041] S3: The dried sample is transferred into a tubular furnace and nitrogen is introduced. The temperature is raised to 350°C. After 6 hours of high-temperature treatment in a nitrogen atmosphere, hydrogen is introduced to continue reducing the catalyst. The temperature is lowered after 6 hours. When the temperature is below 40°C, air is introduced to passivate the catalyst for 8 hours.
[0042] The catalyst was loaded into a fixed bed continuous reactor and the catalyst was evaluated under the above conditions.
[0043] Under the condition of reaction temperature of 220℃, the results of chromatographic analysis of gas samples showed that the conversion rate of CFC-113 was 87%, the selectivity of chlorotrifluoroethylene was 78%, and the selectivity of by-product trifluoroethylene was 21%; after 1000 hours of continuous reaction, the conversion rate of CFC-113 remained at 86%, the selectivity of chlorotrifluoroethylene was 77%, the selectivity of by-product trifluoroethylene was 22%, and the total selectivity of chlorotrifluoroethylene and trifluoroethylene reached 99%.
[0044] Comparative Example 1:
[0045] A hydrodechlorination catalyst, using extruded columnar coconut shell activated carbon as a carrier to prepare a Cu-Pd catalyst with the same loading amount as in Example 1, and the only difference from Example 1 is that:
[0046] Step S1 is replaced by:
[0047] Coconut shell activated carbon powder (~100 mesh, Shanghai Guoyao Reagent Co., Ltd.) was used, and an extrusion aid (containing 2% methyl cellulose, 1% graphite and 2% coal tar) of 5wt% of the activated carbon mass and an appropriate amount of water (~5wt%) were added. The mixture was evenly mixed and 2mm columnar activated carbon was extruded. After the activated carbon and the extrusion aid were carbonized at 800°C, they were used as activated carbon carriers for standby use.
[0048] The rest is the same as in Example 1.
[0049] The above-mentioned activated carbon-supported Cu-Pd active metal component catalyst was loaded into a fixed bed reactor and reacted according to the conditions of Example 1. At a reaction temperature of 220° C., chromatographic analysis results showed that the conversion rate of CFC-113 was 25%, the selectivity of trifluorochloroethylene was 45%, and the selectivity of by-product trifluoroethylene was 45%; after 200 hours of reaction, the conversion rate of CFC-113 was 13%.
[0050] Comparative Example 2:
[0051] A hydrodechlorination catalyst, using extruded activated carbon as a carrier to prepare a Cu-Pd catalyst with the same loading amount as in Example 1, and the only difference from Example 1 is that:
[0052] Step S1 is replaced by:
[0053] The extruded activated carbon was coal-based activated carbon (2 mm columnar, Shanghai Guoyao Reagent Co., Ltd.), washed and dried three times with 8 wt % nitric acid, and used as a carrier. The specific surface area of the activated carbon after acid washing was 1100 m 2 / g, pore volume 0.7cm 3 / g, average pore size 2.8nm, ash content 10%wt (mainly containing oxides of elements such as silicon, iron and aluminum).
[0054] The rest is the same as in Example 1.
[0055] The above-mentioned activated carbon-supported Cu-Pd active metal component catalyst was loaded into a fixed bed reactor and reacted according to the conditions of Example 1. At a reaction temperature of 220° C., the chromatographic analysis results showed that the conversion rate of CFC-113 was 98%, the selectivity of chlorotrifluoroethylene was 91%, and the selectivity of by-product trifluoroethylene was 7%; after 700 hours of reaction, the conversion rate of CFC-113 was 88%, the selectivity of chlorotrifluoroethylene was 92%, and the selectivity of by-product trifluoroethylene was 5%.
[0056] Comparative Example 3:
[0057] A hydrodechlorination catalyst, using columnar coconut shell activated carbon as a carrier to prepare a Cu-Pd catalyst with the same loading amount as in Example 1, the only difference from Example 1 is that:
[0058] Step S1 is replaced by:
[0059] The above coconut shell activated carbon powder (100 mesh, coconut shell, Shanghai Guoyao Reagent Co., Ltd.) was used, and an extrusion aid (2% sodium carboxymethyl cellulose, 1% polyethylene glycol ether and 2% phosphoric acid) with a weight of 5% wt of the activated carbon and an appropriate amount of water (-8%) were added, mixed evenly and extruded into a 2 mm columnar activated carbon, and the activated carbon and the extrusion aid were carbonized at 800° C., and then washed 3 times with 10% nitric acid and used as an activated carbon carrier for standby use;
[0060] The rest is the same as in Example 1.
[0061] The above-mentioned activated carbon was first impregnated with Cu and then with Pd to prepare a Cu-Pd active metal component catalyst, which was loaded into a fixed bed reactor and reacted according to the conditions of Example 1. At a reaction temperature of 220°C, the results of chromatographic analysis showed that the conversion rate of CFC-113 was 45%, the selectivity of trifluorochloroethylene was 40%, and the selectivity of the by-product trifluoroethylene was 58%; after 500 hours of reaction, the conversion rate of CFC-113 was 23%.
[0062] Embodiment 2:
[0063] A hydrodechlorination catalyst, which differs from Example 1 only in that:
[0064] In step S3, the nitrogen sintering temperature is 300°C and the hydrogen reduction temperature is 280°C.
[0065] The rest is the same as in Example 1.
[0066] The catalyst was loaded into a fixed bed reactor and the catalyst was evaluated under the above conditions.
[0067] Under the condition of reaction temperature of 220℃, the chromatographic analysis results show that the conversion rate of CFC-113 is 90%, the selectivity of chlorotrifluoroethylene is 69%, and the selectivity of by-product trifluoroethylene is 30%; after 1000 hours of reaction, the conversion rate of CFC-113 is 90%, the selectivity of chlorotrifluoroethylene is 68%, and the selectivity of by-product trifluoroethylene is 31%. That is, the total selectivity of chlorotrifluoroethylene and trifluoroethylene reaches 99%.
[0068] Embodiment 3:
[0069] A hydrodechlorination catalyst, which differs from Example 2 only in that:
[0070] Use fruit shell activated carbon (3-4 mm, irregular particles, Shanghai Sinopharm Reagent Co., Ltd.) to replace coconut shell activated carbon powder;
[0071] The rest is the same as Example 2.
[0072] The catalyst was loaded into a fixed bed reactor and the catalyst was evaluated under the above conditions.
[0073] At a reaction temperature of 268°C and a mass space velocity of 1.0 h -1 Under the conditions, the chromatographic analysis results showed that the conversion rate of CFC-113 was 70%, the selectivity of chlorotrifluoroethylene was 60%, and the selectivity of by-product trifluoroethylene was 38%; after 1000 hours of reaction, the conversion rate of CFC-113 was 70%, the selectivity of chlorotrifluoroethylene was 60%, the selectivity of by-product trifluoroethylene was 38%, and the total selectivity of chlorotrifluoroethylene and trifluoroethylene reached 98%.
[0074] Embodiment 4:
[0075] A hydrodechlorination catalyst, which differs from Example 3 only in that:
[0076] The support in step S2 is replaced with mesoporous activated carbon (J. Am. Chem. Soc. 2000, 122, 10712-10713).
[0077] The catalyst was loaded into a fixed bed reactor and the catalyst was evaluated under the above conditions.
[0078] At a reaction temperature of 245°C and a mass space velocity of 1.0 h -1 Under the conditions of , the chromatographic analysis results showed that the conversion rate of CFC-113 was 70%, the selectivity of chlorotrifluoroethylene was 80%, and the selectivity of by-product trifluoroethylene was 18%; after 100 hours of reaction, the conversion rate of CFC-113 was 70%, the selectivity of chlorotrifluoroethylene was 80%, the selectivity of by-product trifluoroethylene was 18%, and the total selectivity of chlorotrifluoroethylene and trifluoroethylene reached 98%.
[0079] Embodiment 5:
[0080] A hydrodechlorination catalyst, the preparation method of which comprises:
[0081] S1: Weigh 4.0 g of copper chloride dihydrate and 0.375 g of palladium chloride respectively, dissolve in 52 ml of water, and add 1 ml of hydrochloric acid to adjust the pH to 0.9; impregnate 50 g of granular activated carbon (3-4 mm irregular particles, almond shells, purchased from Shanghai Sinopharm Reagent Co., Ltd.) with the above solution. After immersion at room temperature for 3 hours, place in a vacuum drying oven at 70°C and dry for 30 minutes;
[0082] S2: The dried sample is transferred into a tubular furnace and nitrogen is introduced. The temperature is raised to 380°C. After 6 hours of high-temperature treatment in a nitrogen atmosphere, hydrogen is introduced to continue reducing the catalyst. The temperature is lowered after 6 hours. When the temperature is below 40°C, air is introduced to passivate the catalyst for 8 hours.
[0083] The catalyst was loaded into a fixed bed continuous reactor and the catalyst was evaluated under the above conditions.
[0084] Under the condition of reaction temperature of 230℃, the results of chromatographic analysis of gas samples showed that the conversion rate of CFC-113 was 90%, the selectivity of chlorotrifluoroethylene was 83%, and the selectivity of by-product trifluoroethylene was 15%; after 1000 hours of continuous reaction, the conversion rate of CFC-113 remained at 90%, the selectivity of chlorotrifluoroethylene was 83%, the selectivity of by-product trifluoroethylene was 16%, and the total selectivity of chlorotrifluoroethylene and trifluoroethylene reached 99%.
[0085] Embodiment 6:
[0086] A hydrodechlorination catalyst, which differs from Example 5 only in that:
[0087] In step S3, the nitrogen sintering temperature is 350°C and the hydrogen reduction temperature is 450°C.
[0088] The rest is the same as Example 5.
[0089] The catalyst was loaded into a fixed bed reactor and the catalyst was evaluated under the above conditions.
[0090] Under the condition of reaction temperature of 230℃, the results of chromatographic analysis of gas samples showed that the conversion rate of CFC-113 was 88%, the selectivity of chlorotrifluoroethylene was 90%, and the selectivity of by-product trifluoroethylene was 8%; after 1000 hours of continuous reaction, the conversion rate of CFC-113 remained at 88%, the selectivity of chlorotrifluoroethylene was 91%, the selectivity of by-product trifluoroethylene was 8%, and the total selectivity of chlorotrifluoroethylene and trifluoroethylene reached 99%.
[0091] Embodiment 7:
[0092] The only difference compared with Example 1 is:
[0093] During the catalyst evaluation process, the molar ratio of hydrogen to trichlorotrifluoroethane was 1.5:1.
[0094] Under the condition of reaction temperature of 220℃, the results of chromatographic analysis of gas samples showed that the conversion rate of CFC-113 was 87%, the selectivity of chlorotrifluoroethylene was 86%, and the selectivity of by-product trifluoroethylene was 12%; after 1000 hours of continuous reaction, the conversion rate of CFC-113 remained at 86%, the selectivity of chlorotrifluoroethylene was 86%, the selectivity of by-product trifluoroethylene was 13%, and the total selectivity of chlorotrifluoroethylene and trifluoroethylene reached 99%.
[0095] Embodiment 8:
[0096] The only difference compared with Example 7 is:
[0097] In step S3, the catalyst is treated with high-temperature nitrogen and then loaded into a reactor for reduction. After the reduction, trifluorotrichloroethane and hydrogen are directly introduced to react without catalyst passivation and re-reduction.
[0098] In a fixed bed continuous reactor, at a reaction temperature of 225°C, the results of chromatographic analysis of gas samples showed that the CFC-113 conversion rate was 88%, the trifluorochloroethylene selectivity was 85%, and the by-product trifluoroethylene selectivity was 14%; after 1000 hours of continuous reaction, the CFC-113 conversion rate remained at 87%, the trifluorochloroethylene selectivity was 86%, the by-product trifluoroethylene selectivity was 13%, and the total selectivity of trifluorochloroethylene and trifluoroethylene reached 99%.
[0099] It can be seen from the above examples that the preparation method based on the Cu-Pd loaded activated carbon catalyst can play a role in adjusting the selectivity of trifluorochloroethylene and trifluoroethylene without adjusting the Cu-Pd ratio and adding additional additives. The selectivity of trifluorochloroethylene can be adjusted over a wide range, and the total selectivity of trifluorochloroethylene and trifluoroethylene is maintained at 98% and above. Directly using granular activated carbon as a carrier can avoid the influence of activated carbon extrusion molding and molding aids on catalyst preparation and reducing reaction conversion rate, and the carrier activated carbon has no post-modification and post-doping, which is conducive to reducing the preparation cost of the catalyst. The Cu-Pd loaded activated carbon catalyst prepared by the above method can be used in the reaction of preparing trifluorochloroethylene and trifluoroethylene by hydrogenation of trifluorotrichloroethane.
[0100] The above description of the embodiments is to facilitate the understanding and use of the invention by those skilled in the art. It is obvious that those skilled in the art can easily make various modifications to these embodiments and apply the general principles described herein to other embodiments without creative work. Therefore, the present invention is not limited to the above embodiments, and improvements and modifications made by those skilled in the art based on the disclosure of the present invention without departing from the scope of the present invention should be within the scope of protection of the present invention.
Claims
1. A method for preparing a hydrodechlorination catalyst, characterized in that: include: The palladium source and the copper source are impregnated on the activated carbon carrier, dried, and then pre-treated by heating in an inert atmosphere, reduced in a hydrogen atmosphere, and passivated in an air atmosphere. The loading amount of palladium on the activated carbon carrier is 0.5-0.1 wt %, and the loading amount of copper on the activated carbon carrier is 5-0.1 wt %.
2. The method for preparing a hydrodechlorination catalyst according to claim 1, characterized in that: The specific surface area of the activated carbon carrier is 500 to 1200 cm 2 / g, pore volume 0.5~2m 3 / g, average pore size 1-8nm, ash content less than 0.5-15wt%; The carbon source of the activated carbon carrier is selected from at least one of coal, coconut shell, fruit shell, asphalt or phenolic resin.
3. The method for preparing the hydrodechlorination catalyst according to claim 1, characterized in that: The palladium source and the copper source are loaded on the activated carbon carrier by co-impregnation or step-by-step impregnation; when step-by-step impregnation is adopted, the copper source is loaded first, and then the palladium source is loaded after drying.
4. The method for preparing a hydrodechlorination catalyst according to claim 1, characterized in that: The palladium source is selected from at least one of palladium chloride, palladium nitrate or palladium acetate; the copper source is selected from at least one of copper nitrate, cupric chloride, cuprous chloride, cupric acetate or copper sulfate.
5. The method for preparing the hydrodechlorination catalyst according to claim 1, characterized in that: The loading amount of palladium on the activated carbon carrier is 0.5-0.2 wt %; the loading amount of copper on the activated carbon carrier is 5-0.5 wt %.
6. The method for preparing a hydrodechlorination catalyst according to claim 1, characterized in that: The drying adopts at least one of normal pressure drying, negative pressure vacuum drying and microwave drying, and the drying temperature is 40-100°C.
7. The method for preparing a hydrodechlorination catalyst according to claim 1, characterized in that: In the heating pretreatment, the pretreatment temperature is 100-600° C.; the inert atmosphere is nitrogen or argon.
8. The method for preparing a hydrodechlorination catalyst according to claim 1, characterized in that: In the reduction treatment, the reduction temperature is 250-600°C.
9. The method for preparing a hydrodechlorination catalyst according to claim 1, characterized in that: In the passivation treatment, the treatment temperature is room temperature to 150°C.
10. Use of a hydrodechlorination catalyst prepared by the method according to any one of claims 1 to 9, characterized in that: The hydrodechlorination catalyst is used for the hydrogenation reduction reaction of 1,1,2-trifluorotrichloroethane.
Citation Information
Patent Citations
Process for preparing chlorotrifluoroethylene and trifluoroethylene starting with 1, 1, 2-trichloro-1, 2, 2-trifluoroethane and catalytic composition used in this process
CN1065261A
Catalyst for preparing trifluorochloroethylene and trifluoroethylene by using CFC-113 catalytic hydro-dechlorination and its preparation method
CN1460549A
Cited By
Trifluorochloroethylene continuously prepared based on microchannel reactor and preparation method thereof
CN121537246A